Olfactory-induced synesthesias a review and model. [article]. - Stevenson, Richard J.
Recent reviews of synesthesia concentrate upon rare neurodevelopmental examples and exclude common olfactory-induced experiences with which they may profitably be compared. Like the neurodevelopmental synesthesias, odor-induced experiences involve different sensory modalities; are reliable, asymmetric (concurrents cannot induce), and automatic; and the inducer-concurrent relationship is learnt. Unlike neurodevelopmental synesthesias, these experiences are universal and their synesthetic nature goes unrecognized. Olfaction's ability to universally induce concurrents may result from its unique neuroanatomy, affording dual access to neocortex. We propose that concurrents arise here via a twofold process: by direct neocortical activation, which recovers a configural memory, and by attribution of this memory to the olfactory modality by thalamic attentional processes. The implications of this for other forms of synesthesia are then examined. -- (from the author)